PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO DARA PLASTIK CISEENG BOGOR - Saputri Fatmala; Surti Wardani (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of price and product quality on purchasing decisions at the Dara Plastik Ciseeng Bogor Store. This research method uses a causal associative method with a quantitative approach. in this study, samples were taken using non-probability sampling techniques using the Incidental method and quota sampling with a sample size of 100. The data were processed and analyzed using descriptive analysis tests, research instrument tests, classical assumption tests, quantitative analysis, simple linear regression tests, multiple linear regression tests, correlation coefficient tests, determination coefficient tests, t tests, and F tests, using SPSS 26. The results of the study Price has a positive and significant effect on Purchasing Decisions at the Dara Plastik Ciseeng Store. significance value (0.107> 0.05) then this test is Normal. Regression equation Y = 17.679 + 0.695 X1 + 0.180 X2. Multiple Correlation Coefficient R 0.641 Price and Product Quality have a strong relationship Purchasing Decisions. R Square value 41.1% Price and Product Quality affect purchasing decisions. t count value > t table ( 7.268 > 1.661 ) and Sig. value < 0.05 or (0.000 < 0.05 ). Product Quality has a significant effect on Purchasing Decisions at Dara Plastic Ciseeng Store. t count value > t table or ( 4.918 > 1.661 ) and Significant value < 0.05 or (0.000 < 0.05 ) while the Price and Product Quality variables have a positive and significant effect on purchasing decisions at Dara Plastic Ciseeng Bogor Store. f count value > f table ( 33.872 > 3.09 ) and Sig. < 0.05 or ( 0.000 < 0.05 ). Thus Price and Product Quality on Purchasing Decisions at Dara Plastic Ciseeng Bogor Store.